Interfacial Properties of Octenyl Succinic Anhydride-Starch Decorated Zein Particles and Stability of Pickering Emulsion Stabilized with It - LEI Dandan, WANG Limin, ZHANG Wen, ZHAO Pei, QIAN Xiaoqing, QU Ao, WU Zijian (Shipin Kexue, 2023)
In order to improve the ability of solid zein particles to stabilize Pickering emulsions, octenyl succinic anhydride (OSA)-modified starch was used to modify zein. Zein-OSA starch composite particles were prepared by solvent-antisolvent precipitation method. The interaction between zein and OSA starch and the size and structure of the composite particles were studied, and the effects of the mass ratio of zein to OSA starch on the particle size distribution, storage stability, pH stability and rheological properties of Pickering emulsion stabilized with the composite particles were explored. The results showed that OSA starch could modify zein through non-covalent interactions including electrostatic interaction, hydrogen bonding and hydrophobic interaction, changing the secondary structure of zein and improving its hydrophilicity. The composite particles with zein to OSA starch ratio of 1:3 had the smallest average particle size (163.3 nm) and PDI (0.177), and its contact angle was 87.4°, which indicated that the particles had nearly neutral wettability and were more suitable for stabilizing Pickering emulsions. Meanwhile, Pickering emulsions stabilized by the composite particles had the smallest particle size distribution and the highest storage modulus, loss modulus and apparent viscosity, indicating that OSA starch modification could regulate the interfacial properties of zein composite particles and consequently of Pickering emulsions. The above studies show that the interfacial modification of zein can improve the stability of its solid particles and consequently of Pickering emulsions. This study provides theoretical support for further expanding the comprehensive utilization of zein in emulsion systems.